PENERAPAN MODEL PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV MIS AT-TAQWA MALIFUT - Gufran Usman; Muhammad Refki Yunus (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to determine the improvement of the science learning outcomes in 4th grade students of MIS At-TaqwaMalifut by applying the Index Card Match Learning Model. The research design was Classroom Action Research (PTK). The subjects of this study were 26 of 4th grade students in MIS At-Taqwa, Malifut Sub-district. The data collection instrument in the first cycle consisted of 6 essay questions with a maximum score of 55, and in the second cycle consisted of 6 essay questions with a maximum score of 65. The data analysis and data collection techniques were carried out through observation and tests. The observation sheet was used to obtain data of the researchers’ and students’activities every time the action took place, while the test was used to assess students’ learning outcomes. After the research data were analyzed descriptively, it was found that in the first cycle the students’ activity was 64.42% and in the second cycle, it increased to 74.27%. Meanwhile, the research activity in the first cycle was 68.16% and the second cycle increased to 79.16%. The student test results in the first cycle showed that the students who passed the passing score were18 students or 69.23% and in the second cycle increased to 21 students who passed the passing score classically or 80.76%. This showed that by applying the Index Card Match learning model, it could improve the learning outcomes of 4th grade students in science subjects at MIS At-Taqwa Malifut.